Challenges in Adoption of Digital Health Technology among Educated Youth in Pakistan - Dr. Rahla Rahat; Dr. Adnan Adil; Ayesha Siddiqa Bugvi (Journal of Peace, Development and Communication, 2022)
This study attempts to examine the challenges in the adoption of digital health technology among educated youth in Pakistan. Using qualitative research methods, opinions of male and female students of public and private sector universities in Islamabad were gathered through eight Focus Group Discussions (FGDs). The study themes included: Complexity of language and medical terminology on the internet, lack of Information and Communication Technology (ICT) skills, less reliability of different websites, and threat to privacy. The study found that several factors such as poor facilitations conditions, institutional negligence, problematic medical jargon, online frauds, and privacy insensitivity are hampering the access to eHealth services among students of universities in Islamabad. As the global health systems are moving towards eHealth services, the lack of technological knowledge of the patients may harm their access to health services. Thus, there is a need to minimize the barriers to digital health education at the institutional level.